Where is Grandpa? - Barron, T. A.; Soentpiet, Chris K. (New York : Philomel Books, 2000)
As his family reminisces after his beloved grandfather's death, a boy realizes that his grandfather is still with him in all the special places they shared.
Keywords: Grandfathers -- Fiction; Death -- Fiction; Grief -- Fiction